2006
DOI: 10.1007/bf03256495
|View full text |Cite
|
Sign up to set email alerts
|

Attitude dynamics of satellites orbiting an asteroid

Abstract: Attitude motion of satellites orbiting an asteroid is examined. The highly irregular shape of the asteroids along with their rotational states can lead to very interesting attitude dynamics. As a start, the case of uniform rotation of the asteroid is examined and attention is focused on planar attitude motion (pitch). Four asteroids, Vesta, Eros, Gaspra, and Castalia, are considered. For the case of circular equatorial orbits, the radius for which resonant pitch oscillations are excited, is determined. It is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…For this study, satellite attitude dynamics derived in Refs. [14,15] are considered. (Readers may refer to [14,15] for the details.)…”
Section: Attitude Dynamics Of Asteroid-orbiting Spacecraftmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, satellite attitude dynamics derived in Refs. [14,15] are considered. (Readers may refer to [14,15] for the details.)…”
Section: Attitude Dynamics Of Asteroid-orbiting Spacecraftmentioning
confidence: 99%
“…Additionally, researchers have analyzed the attitude dynamics of spacecraft in asteroids' gravitational fields [14][15][16][17][18][19]. The authors showed that irregularly-shaped asteroids can cause attitude resonance [14][15][16] and chaotic phenomenon [17]. The authors of [18] found natural Sun-synchronous orbits with Sun-tracking attitude motions for an orbit-attitude coupled system around a small rotating body [18].…”
Section: Introductionmentioning
confidence: 99%
“…We also can obtain the pitch controller response as Figure 32. Compared with the attitude stability analysis in references [10][11][12][13], closed-loop controllers are proposed to make the spacecraft attitude angles tracking the desired attitude as (42) and reach the null state as time increases. Moreover, from simulation results one can obtain the control law neutralizing the effects of asteroid shape and mass distributions and orbital eccentricity as well as external disturbances and uncertainties described as (43).…”
Section: Adaptive Backstepping Sliding Mode Controlmentioning
confidence: 99%
“…Riverin and Misra have proposed the attitude motion of the spacecraft depending heavily on the shape of the asteroid and the rotational state [12]. Then Misra and Panchenko have found the radius for which resonant pitch oscillations, considering the general three-dimensional attitude motion in 2006 [13]. Riverin and Misra have examined the spacecraft pitch motion assuming the spacecraft is in an equatorial orbit but spacecraft attitude control algorithms have not been perfectly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This point mass model can be improved by considering the orbit-attitude coupling, especially in the case of a large-sized spacecraft. The dynamical model with orbit-attitude coupling can also improve the traditional attitude dynamics near asteroids [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%